The Existing Practice of Activity-Based Classroom Instruction in Sainamaina Municipality - Bhattarai, Taranath (Education and Development, 2024)
This study aims at identifying the status of activity-based classroom instruction in the context of government schools in Sainamaina Municipality and analyzes the reasons behind the existing status of the activity-based classroom instruction. It also suggests some strategies for the implementation of the activity-based classroom instruction. Based on qualitative method, the data were generated through classroom observation and semi- structured interview. The collected data were analyzed by using thematic analysis under interpretative paradigm. The study has revealed a poor status of the application of activity-based classroom instruction in the study area along with the issues of teacher development, administration, local needs, examination system and also emphasizes on addressing the development of contextual activity-based classroom instructions.